Combined analyses of transcriptome and metabolome reveal the mechanism of exogenous strigolactone regulating the response of elephant grass to drought stress - Zhou, Jing; Liu, Yijia; Li, Yan; Ling, Wenqing; Fan, Xiaoyu; Feng, Qixian; Ming, Ray; Yang, Fulin (Frontiers in Plant Science, 2023)
Elephant grass is widely used in feed production and ecological restoration because of its huge biomass and low occurrence of diseases and insect pets. However, drought seriously affects growth and development of this grass. Strigolactone (SL), a small molecular phytohormone, reportedly participates in improving resilience to cope with arid environment. But the mechanism of SL regulating elephant grass to response to drought stress remains unknown and needs further investigation. We conducted RNA-seq experiments and identified 84,296 genes including 765 and 2325 upregulated differential expression genes (DEGs) and 622 and 1826 downregulated DEGs, compared drought rehydration with spraying SL in roots and leaves, respectively. Combined with targeted phytohormones metabolite analysis, five hormones including 6-BA, ABA, MeSA, NAA, and JA had significant changes under re-watering and spraying SL stages. Moreover, a total of 17 co-expression modules were identified, of which eight modules had the most significant correlation with all physiological indicators with weighted gene co-expression network analysis. The venn analysis revealed the common genes between Kyoto Encyclopedia of Genes and Genomes enriched functional DEGs and the top 30 hub genes of higher weights in eight modules, respectively. Finally, 44 DEGs had been identified as key genes which played a major role in SL response to drought stress. After verification of its expression level by qPCR, six key genes in elephant grass including PpPEPCK, PpRuBPC, PpPGK, PpGAPDH, PpFBA, and PpSBPase genes regulated photosynthetic capacity under the SL treatment to respond to drought stress. Meanwhile, PpACAT, PpMFP2, PpAGT2, PpIVD, PpMCCA, and PpMCCB regulated root development and phytohormone crosstalk to respond to water deficit conditions. Our research led to a more comprehensive understanding about exogenous SL that plays a role in elephant grass response to drought stress and revealed insights into the SL regulating molecular mechanism in plants to adapt the arid environment.